PENGARUH KARAKTERISTIK PERUSAHAAN DAN KINERJA KEUANGAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dias, Darmiatun Dias Darmiatun; ', Caska Caska; ', Gusnardi Gusnardi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to determine the effect of Firm Size, leverage, board of commissioner size, and ROA on corporate social responsibility disclosure.This research conducted to mining companies listed in indonesian Stock Exchange 2011-2013 period wiht 39 sample obtained using purposive sampling method. The analysis technique used in this study is the technique of multiple linier regression analysis. The result showed that the variables firm size have a significant effect on the corporate social responsibility disclosure while variables leverage, board of commissioner size and ROA does not significant effect to corporate social responsibility disclosure of mining companies listed in Indonesian Stock Exchange 2011-2013 period.Keywords: Firm Size, leverage, board of commissioner size, ROA, and corporate social responsibility disclosure.